“diseño de un plan estratégico de marketing y su efecto en la participación de mercado de la empresa 1434 s. a. c.” - Reaño Ortega, Ricardo José (2016)
This thesis entitled “Design of a Strategic Marketing Plan and its effect on the market share of the company 1434 S. A. C.”, its main objective is to determine the effect on the market share of the company in the city of Trujillo, by implementation of marketing strategies. It began developing strategic planning for the company. First the strategic direction was established. Then, it carried out the external and internal analysis of the company, determining the strengths, weaknesses, opportunities and threats. Subsequently, different matrices (SWOT, PEYEA, BCG and the main strategy) were developed to identify the ideal strategies to meet and / or reformulate the proposed objectives. To develop the Strategic Marketing Plan, we start from the delimitation of market, then, market research is done to find market segments, select the target and know their buying behavior. The positioning of the company is established and brand equity. The marketing plan ended setting product, price, place and promotion strategies. After, the Strategic Marketing Plan was economically, obtaining a NPV of S /. 4,032.06 and an IRR of 61.54%. With sales information of the company and the industry, this data is projected until 2018, concluding that the Strategic Marketing Plan will generate in the company an average annual increase in the market share of 7.00% in the city of Trujillo, in 2018 it is 2.09%.